Regulation, concentration and competition in financial intermediation - Schargrodsky, Ernesto (1999)
The strengthening of prudential regulation has, in general, led to increased concentration of the financial sector. While better prudential regulation may deliver a benefit in terms of higher solvency, it is usually understood that more concentration, in general, implies higher spreads. Thus, there is a view that these prudential measures imply a tradeoff between solvency and competition. In this paper we want to argue that such a tradeoff does not necessarily exist. We present a model in which product differentiation decreases with concentration potentially inducing more intense competition, and therefore lower spreads. We provide evidence from a cross section of countries in favor of this alternative view.